MODERASI BERAGAMA: SIKAP TOLERANSI SISWA SEKOLAH DASAR - Nisa, Ikhfah Chairun; Siregar, Nasyariah (Faculty of Educational Sciences,Universitas Islam Negeri (UIN) Syarif Hidayatullah Jakarta, 2025)
This research aims to describe the religious moderation tolerance attitude of students at State Elementary School 028/IV Jambi City. This research uses qualitative research with a case study type. The techniques used to collect data are observation, interviews and documentation. The selection of subject used purposive sampling. Data analysis techniques include data reduction, data presentation and drawing conclusions. The validity of the data in this research uses triangulation techniques. The results of this research show that the attitude of religious moderation tolerance of students at State Elementary School 028/IV in Jambi City is very good. Students already respect and respect each other's religious differences. School activities, such as group worship according to one's religion and other routine activities, also support the creation of a tolerant environment. Teachers and school residents also play an active role in educating and guiding students with the values ​​of tolerance. The attitude of students at Elementary School 028/IV Jambi City does not differentiate between friends based on religion, they care about always reminding friends to carry out their religious obligations. Three main indicator that can be drawn are students' attitudes of tolerance, moderation through peace, awareness and respect for themselves and others.